2014
DOI: 10.1128/iai.01940-14
|View full text |Cite
|
Sign up to set email alerts
|

The Subcellular Location of Ovalbumin in Plasmodium berghei Blood Stages Influences the Magnitude of T-Cell Responses

Abstract: bModel antigens are frequently introduced into pathogens to study determinants that influence T-cell responses to infections. To address whether an antigen's subcellular location influences the nature and magnitude of antigen-specific T-cell responses, we generated Plasmodium berghei parasites expressing the model antigen ovalbumin (OVA) either in the parasite cytoplasm or on the parasitophorous vacuole membrane (PVM). For cytosolic expression, OVA alone or conjugated to mCherry was expressed from a strong con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…To determine the anatomical relationship between myelomonocytic cells and iRBCs during the development of ECM, we infected LysM gfp/+ mice with recombinant PbA expressing mCherry and OVA (PbA-OVA-mCherry) [45]. In symptomatic mice at d6 p.i., we observed fluorescent iRBCs adherent to cerebral vasculature (Fig 2B; S3 Movie), similar to what is found in human CM patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the anatomical relationship between myelomonocytic cells and iRBCs during the development of ECM, we infected LysM gfp/+ mice with recombinant PbA expressing mCherry and OVA (PbA-OVA-mCherry) [45]. In symptomatic mice at d6 p.i., we observed fluorescent iRBCs adherent to cerebral vasculature (Fig 2B; S3 Movie), similar to what is found in human CM patients.…”
Section: Resultsmentioning
confidence: 99%
“…PbA.OVA::mCherry hsp70 (PbA-OVA-mCherry) parasites were kindly provided by C. Janse and S. Khan [45]. PbTg (PbA-OVA-GFP) parasites were kindly provided by W. Heath [38].…”
Section: Methodsmentioning
confidence: 99%
“…To measure antigen-specific CD4 + T cell expansion, we utilized a P. yoelii parasite modified to stably express amino acids 51-84 of the LCMV GP under the Hep17 promoter (Supplemental Figure 3A). Expression under the Hep17 promoter localizes peptide expression to the parasitophorous vacuole, and this promoter is active during the erythrocytic stage of infection (29). This LCMV sequence encodes an immunogenic CD4 + T cell epitope presented on I-A b MHC molecules (aa 61-80) (30,31).…”
Section: Cd11bmentioning
confidence: 99%
“…Reduced sporozoite production #69 infections [9,10,[56][57][58]. For example, intravital two-photon microscopy of livers of mice infected with P. berghei parasites that express OVA and GFP in their cytoplasm showed that transferred OVA-specific CD8 + T cells recognize and forms clusters around infected hepatocytes, leading to the elimination of the intra-hepatic parasites [56].…”
Section: Transgenic Parasites Expressing Reporter Proteinsmentioning
confidence: 99%
“…These parasites have been used to visualize and analyze parasite growth and development in vitro and in vivo and have been valuable tools to analyze cellular and molecular features of malaria parasite biology (reviewed in [4][5][6][7]). Transgenic rodent parasites have also been used to provide mechanistic insights into host-parasite interactions that regulate host (immune) responses to infection or those that mediate malarial pathology [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%